High recurrence of lymphedema and influencing factors in discharged breast cancer patients during the COVID‐19 pandemic: A multicenter, cross‐sectional survey. (11th May 2022) - Peng, Xin; Chen, Renwang; Rao, Zhenli; Yang, Yi; Yan, Yunli; Xia, Ying; Wang, Ting; Wang, Jianying; Lu, Fang; Pan, Hong; Liu, Yan; Cheng, Jing; et al.
Abstract: Background: There has been a delay in the detection and treatment of lymphedema in breast cancer patients during the lockdown owing to quarantine and limited social activity. Moreover, this scenario has caused psychosocial issues in these patients. Given that there is scarce information on the prevalence and influence of lymphedema during the coronavirus disease (COVID‐19) pandemic, we aimed to estimate the prevalence of lymphedema recurrence and its influencing factors among discharged breast cancer patients during the COVID‐19 pandemic. Methods: This was a multicenter, cross‐sectional, hospital‐based survey of discharged breast cancer patients was conducted during the COVID‐19 pandemic in eight first‐class hospitals in Wuhan, China. The Norman Questionnaire was used to assess lymphedema. Univariable and multivariable binary logistic regression analyses were performed to identify factors influencing moderate or severe lymphedema. Differences in living characteristics, anxiety, and depression were compared between the no/mild lymphedema group and the moderate/severe lymphedema groups. Preferences for lymphedema management during the pandemic were determined. Results: Overall, 202 patients were included in this study, and 191 of them reported recurrent lymphedema (prevalence: 94.6%, 95% confidence interval [CI] 90.5% to 97.3%). Among them, 134 and 57 had mild and moderate/severe lymphedema, respectively. In 191 patients, the main symptoms were swelling (140; 69.3%) and pain (56, 27.7%). Multivariable regression showed that older age (odds ratio [OR], 1.06; 95% CI: 1.02–1.10), radical surgery (OR = 4.35, 95% CI: 1.54–12.50), and fully complete radiotherapy (OR = 2.62, 95% CI: 1.17–5.87, p  = 0.019) were associated with an elevated risk of moderate/severe lymphedema. The moderate/severe lymphedema group experienced a higher rate of anxiety and depression than the no/mild lymphedema group did. Patients equally preferred treatment in the hospital and self‐care at home. Conclusion: During the COVID‐19 pandemic, high prevalence of lymphedema was observed in patients Age, radical surgery and fully completed radiotherapy were associated with increased risk of severer lymphedema. Meanwhile, the patients with severe lymphedema experienced psychological distress. While the Covid‐19 pandemic was still raging, continuous efforts should be made to identify patient at risk of lymphedema and distribute feasible guidance and education for self‐management in lymphedema.